A new theropod dinosaur from the Early Jurassic of South Africa and its implications for the early evolution of theropods - Yates, Adam M. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2005)
A new theropod, Dracovenator regenti, from the upper Elliot Formation is described, based upon a fragmentary skull. It can be diagnosed on the basis of a bilobed fossa on the lateral surface of the premaxilla that is connected to the alveolar margin by a narrow channel, the presence of a deep, oblique, lateral notch on the articular and hypertrophied dorsal processes on the articular. Other aspects of its morphology display a mosaic of coelophysoid and advanced theropod characteristics. A cladistic analysis of basal Theropoda, including the new taxon finds that the new taxon is closely related to Dilophosaurus wetherilli and Zupaysaurus rougieri although the clade formed by these three taxa is not robustly supported. It also finds that Coelophysoidea sensu lato is paraphyletic with respect to Ceratosauria + Tetanurae but that this topology is not a significantly better explanation of the data than an inclusive, monophyletic Coelophysoidea.